Wearable co-thinking device to assist strawberry packaging task - Osamu Fukuda; Wen Liang Yeoh; Yuta Esaki; Jin Yien Lee; Mitsuru Higashimori; Makoto Kaneko; Satoshi Muraki (Scientific Reports)
Abstract This study develops a wearable co-thinking device to support strawberry packaging, ultimately alleviating the workload on agricultural workers and boosting productivity. This innovative device, worn by the worker, can recognize, analyze, and collaborate with the worker in real time. This device can significantly enhance work performance and reduce the mental load/burden of workers. By utilizing smart glasses and a mechanical gripper, the worker can efficiently pick and package strawberries while accessing pertinent information displayed on the smart glasses, ensuring a streamlined and hygienic packaging process. The most significant feature of this system is its ability to seamlessly integrate system-generated decisions with human input, resulting in optimal task performance. Through rigorous experiments, we validated the effectiveness and practicality of this developed system. Our findings indicate a significant reduction in both the time taken to complete the packaging task and number of times the worker physically handled the strawberries when utilizing the system compared to when performing the task manually ( $$p<0.01$$ ). Furthermore, our research demonstrates that the quality of the packaged strawberries, in terms of weight and ripeness, remains consistent with meticulous manual packaging methods involving the use of an electronic scale. Additionally, the perceived mental workload of the worker, assessed using NASA-TLX, revealed a substantial decrease in mental demand (MD) at $$p<0.01$$ , as well as temporal demand (TD), effort (EF), and frustration level (FR) at $$p<0.05$$ . Moreover, our study highlights the adaptability and efficiency of workers in responding to system errors, such as missing ripe or blemished strawberries, by combining system-generated suggestions with human judgment.